Self-cleaning van der Waals lamination for two-dimensional electronics - Chang Liu; Shuimei Ding; Xudong Wang; Guichen Teng; Jinhua Zeng; Ying Zhang; Qianru Zhao; Huiting Wang; Binmin Wu; Shuaiqin Wu; Yan Chen; Tie Lin; et al. (Science Bulletin, 2026)

Protein-based functional materials for gold ion separation: Mechanisms, challenges and future perspectives - Qingmin Yang; Yingying Zhang; Yuanhang Yang; Xiaoyun Zhang; Yongliang Ding; Arif Muhammad; Guichen Liu; Facui Yang; Renyuan Song; Yanfang Tai; Peng Yang; Jian Zhao (Journal of Environmental Chemical Engineering, 2025)

Finite-time output feedback control of unmanned marine surface vessels with rotatable thrusters and propellers under deception attacks in an IoT environment - Xiangfei Meng; Guichen Zhang; Bing Han; Yanji Liu; Mengwei Chen; Run Lu (Ocean Engineering, 2025)

An efficient approach for extended shakedown analysis of structures under cyclic dynamic loading - Guichen Zhang; Heng Peng; Zerui Chen; Yinghua Liu; Haofeng Chen (Engineering Structures, 2025)

Protein/polysaccharide composite nanocoating based on amyloid-like aggregation for fresh-cut fruits preservation - Guichen Liu; Rong Liu; Chengyu Fu; Xiang Hu; Ke Li; Luke Yan; Peng Yang; Jian Zhao (Chemical Engineering Journal, 2025)

Adaptive Positioning Control of Multi-Point Moorings with Disturbance Observation Under Input Constraints - Run Lu; Guichen Zhang; Ru Liu; Chaojian Gao; Wei Chen; Huanglong Fu (Journal of Marine Science and Engineering, 2024)
In the presence of dynamic uncertainties, external time-varying disturbances, and limited inputs to the multi-point mooring system (MPMS) of a floating offshore platform (FOP), this paper proposes a robust adaptive dynamic surface (RADS) control method incorporating a disturbance observer. A disturbance observer is designed to estimate the unknown time-varying disturbance and apply feedforward compensation to the control variable. Simultaneously, the adaptive law of the σ-corrected leakage term is employed to estimate the bound of the disturbance observation error, thereby enhancing positioning accuracy. An auxiliary dynamic system (ADS) is then introduced to address input constraints, while the differential explosion problem associated with the traditional inversion method is resolved through the integration of the dynamic surface control (DSC) algorithm. The Lyapunov function is utilized to demonstrate that the controller ensures the consistent ultimate boundedness of all signals within the closed-loop system. Finally, a simulation experiment was conducted based on the eight-point mooring platform of the “Kantan3”, and the positioning accuracy reached 3%, which is higher than the specification requirements of the classification society. The results indicate that the designed controller achieves higher positioning accuracy and improved anti-interference performance and has been put into practical application on “Kantan3”.

Topological rearrangement-derived edge-sharing [MO6] motifs on perovskite oxide for optimizing O-O bonding in water oxidation - Guichen Gao; Guangshe Li; Ming Ya; Nan Liu; Wei Shen; Pinxian Xi; Luyi Sun; Liping Li (Chemical Engineering Journal, 2024)

Stability, rheological behavior and microstructure of Pickering emulsions co-stabilized by soy protein and carboxymethyl chitosan - Guo Huang; Guichen Liu; Zejian Xu; Lianzhou Jiang; Yan Zhang; Xiaonan Sui (Food Hydrocolloids, 2023)

The Arabidopsis nucleoporin NUP1 is essential for megasporogenesis and early stages of pollen development - Shuguang Bao; Guangshuang Shen; Guichen Li; Zhikang Liu; Muhammad Arif; Qingqing Wei; Shuzhen Men (Plant Cell Reports, 2019)